2013
DOI: 10.1016/j.canlet.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of DNA adducts: The transition from 32P-postlabeling to mass spectrometry

Abstract: The technique of 32P-postlabeling, which was introduced in 1982 for the analysis of DNA adducts, has long been the method of choice for in vivo studies because of its high sensitivity as it requires only <10 μg DNA to achieve the detection of 1 adduct in 1010 normal bases. 32P-postlabeling has therefore been utilized in numerous human and animal studies of DNA adduct formation. Like all techniques 32P-postlabeling does have several disadvantages including the use of radioactive phosphorus, lack of internal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 88 publications
0
48
0
Order By: Relevance
“…Our results showed that the BPDE-dG adduct has very similar trends with total DNA adducts. In future studies, high resolution mass spectrometry (Klaene et al 2012) or a combination of 32 P-postlabeling assay and mass spectrometry should be considered in detection and structure identification of DNA adducts (Farmer and Singh 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the BPDE-dG adduct has very similar trends with total DNA adducts. In future studies, high resolution mass spectrometry (Klaene et al 2012) or a combination of 32 P-postlabeling assay and mass spectrometry should be considered in detection and structure identification of DNA adducts (Farmer and Singh 2008). …”
Section: Discussionmentioning
confidence: 99%
“…28 Over the years, sensitivity has continued to improve 6,14 as different research groups have focused on optimization of DNA adduct detection methods with MS [30][31][32][33][34][35][36][37] , including research into non-manual data mining and sequencing to locate DNA adduction sites. 38,39 Due to ongoing technical advancements and the use of stable isotope labeled internal standards, MS currently offers a reliable tool to measure low DNA adduct levels with the highest specificity. 12,14,27,28 Coupling of MS with LC by means of the electrospray interface (ESI) has enabled analysis of DNA adducts in very complex biological matrices 40 , whilst avoiding complex and labour-intensive sample preparation with derivatization for the initially envisioned use of GCcouplings.…”
Section: Mass Spectrometry As the Methods Of Choice For Dna Adductomicsmentioning
confidence: 99%
“…However, those methods are unable to provide information on the structure of DNA adducts, leading to some degree of ambiguity in the identities of unknown DNA adducts [6,7]. In addition, because of exposure to complicated mixtures of environmental contaminants in human exposure scenario, DNA adducts in human samples are often unknowns [8].…”
Section: Introductionmentioning
confidence: 99%